Evaluation of 5G NR NSA Deployment on FR1 (Sub-6 GHz) in Bukittinggi - Sri Yusnita; Siska Aulia; Dikky Chandra; Zurnawita; Miro Dhino Laskar Ashanto (Andalas Journal of Electrical and Electronic Engineering Technology, 2026)
This study evaluates the deployment of 5G New Radio (NR) Non-Standalone (NSA) operating on Frequency Range 1 (FR1) Sub-6 GHz in Bukittinggi, Indonesia. Field measurements were conducted using drive test methods to assess key performance indicators, including RSRP, RSRQ, SINR, and throughput. The results show that all measured RSRP values exceed –95 dBm, indicating good signal coverage across the test area. Approximately 71% of SINR samples are above 0 dB and 80% of RSRQ values exceed –17 dB, reflecting relatively stable channel conditions. However, 77% of throughput measurements remain below 10 Mbps, suggesting that achievable data rates remain moderate despite good signal quality. The analysis indicates that SINR has a stronger impact on throughput compared to RSRP and RSRQ. Although 5G NR NSA demonstrates superior signal quality compared to LTE, 4G LTE achieves higher data speeds at the measurement location. These findings highlight the influence of NSA architecture, bandwidth limitations in FR1 Sub-6 GHz, and network optimization factors on overall 5G performance.